BsEXLX of engineered Trichoderma reesei strain as dual-active expansin to boost cellulases secretion for synergistic enhancement of biomass enzymatic saccharification in corn and Miscanthus straws. (May 2023) - Xu, Chengbao; Xia, Tao; Peng, Hao; Liu, Peng; Wang, Yihong; Wang, Yanting; Kang, Heng; Tang, Jingfeng; Nauman Aftab, Muhammad; Peng, Liangcai
Highlights: A desirable engineered TrEXLX10 strain secretes active BsEXLX/expansin protein. The expansin is of highly binding activity with wall polysaccharides and lignin. TrEXLX10 secretes active cellulases and xylanases by expansin stabilization. High yield hexoses released by enzymatic hydrolysis and expansin coactivation. A model for expansin dual-active roles in enzymes secretion and biomass digestion. Abstract: In this study, bacterial BsEXLE1 gene was overexpressed into T. reesei (Rut-C30) to generate a desirable engineered TrEXLX10 strain. While incubated with alkali-pretreated Miscanthus straw as carbon source, the TrEXLX10 secreted the β-glucosidases, cellobiohydrolases and xylanses with activities raised by 34%, 82% and 159% compared to the Rut-C30. Supplying EXLX10-secreted crude enzymes and commercial mixed-cellulases for two-step lignocellulose hydrolyses of corn and Miscanthus straws after mild alkali pretreatments, this work measured consistently higher hexoses yields released by the EXLX10-secreted enzymes for synergistic enhancements of biomass saccharification in all parallel experiments examined. Meanwhile, this study detected that the expansin, purified from EXLX10-secreted solution, was of exceptionally high binding activities with wall polymers, and further determined its independent enhancement for cellulose hydrolysis. Therefore, this study raised a mechanism model to highlight EXLX/expansin dual-activation roles for both secretion of stable biomass-degradation enzymes at high activity and biomass enzymatic saccharification in bioenergy crops.